Answer:
The factored from of the equation is (x+4)(x-6)=0.
Explanation:
When solving this problem, we need to find the factored form of this problem. Remember that in factored form, the right-hand side of the equation must equal to 0.
We can simply convert the left-hand side to standard form first:
(x-4)(x+2)=16 --> x²-2x-8= 16.
Now, to set the right-hand side of the equation to 0, we must subtract -16 from both sides:
x²-2x-24=0.
Now, if we convert this to factored form, we will get:
(x+4)(x-6)= 0.
All of the other statements are false. This is the only true statement.